Working in the Creative Economy: The Spatial Dynamics of Employment Risk for Musicians in Toronto - Hracs, Brian Jennings (University of Toronto, 2011)
Over the past decade the introduction of MP3’s, file sharing networks and illegal downloading has fundamentally changed the music industry, structurally and spatially. In the wake of this restructuring it is now estimated that 95% of all musicians in Canada operate independently of record companies (Canadian Independent Recording Artist Association or ‘CIRAA’). Digital technologies afford independent musicians greater freedom and control over how and where they live and work. Although economic geographers have been quick to examine the impact of the so called ‘MP3 Crisis’ on record sales and the major record labels, little is known about how changes at the macro-scale affect the working lives of individual musicians in specific locations. As a result, this dissertation focuses on the employment experiences and spatial dynamics of independent musicians in Toronto. Drawing on sixty-five in-depth interviews with musicians and key informants in the music industry, the thesis documents the intersections between technology, work and space. In particular, the analysis highlights the ways in which the new creative and spatial freedoms, associated with independent music production, are accompanied by intensified competition and employment risk, which musicians experience in an increasingly individualized way. Surviving in the current marketplace requires independent musicians to perform a range of new tasks and exhibit a higher degree of professionalism. Accordingly, the research outlines some of the reasons why some musicians are rejecting and reworking traditional bohemian lifestyles, spatial patterns and risk mediation strategies. In particular, there is growing evidence of new forms of networking and of the increased importance of strategic collaborations between musicians and fashion designers. There are also signs that some musicians are relocating from the downtown core to the surrounding suburbs, and that musical talent is becoming redistributed across the city-region. Ultimately, this dissertation demonstrates the need for specialized policies to incubate and retain creative talent in an increasingly global and digital marketplace.